KONSTRUKSI PENGETAHUAN MASYARAKAT PESISIR WATU ULO MENGENAI EARLY WARNING SYSTEM (EWS) TSUNAMI - Royati, Lia Wida; Handayani, Baiq Lily (Jurnal ENTITAS SOSIOLOGI, 2016)
Based on 2012 Tsunami Master Plan, Jember Regency, East Java, is categorized as a tsunami-phone area.Therefore, BPBD (Regional Board on Disaster Management) of Jember Regency carries out a community capacity building through the establishment DESTANA (Disaster Resilient Village), dissemination of disaster and installatiom of EWS sirens. This research focuses on how the communities' understanding and interpretation on the siren as a medium for tsunami EWS. The research aimed to identify and describe the knowledge construction of Watu Ulo coastal communities about Tsunami EWS sirens using descriptive, qualitative method. Informans were determined by purposive sampling technique. The research used Peter L. Berger's theory of Social Construction of Reality to analyze the knowledge construcion of Watu Ulo coastal communities about the EWS sirens. The result showed that the residents of Watu Ulo have knowledge about the condition of the area which has tsunami potentials as well as nature signs of the tsunami. Constuction of Watu Ulo as a tsunami prone area is strenghened with the installation of EWS sirens as a medium for tsunami warning. The construction of public knowledge about EWS passed through three processes i.e. externalitation, and internalition objectivation. The construction of knowledge establised among Watu Ulo residents on EWS results in: 1) public awareness; 2) public peacefulness despite being in a tsunami prone area. Keyword: Construction, Knowledge, Early Warning System (EWS), Tsunami